The Strategy Implementation of Saudi Enterprises: Case Study of Manufacturing Industry in Riyadh - Alqahtani, Khaled Mohammed (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">There is no doubt that the significant role of strategy played in every company, whether it is a small business or a large corporation. However, the strategy implementation of enterprises in Saudi Arabia has received less attention. Owing to growing public demands and government’s initiatives, manufacturing industry in Saudi Arabia has been regarded as a key sector in strengthening the Kingdom’s economic position. Therefore, this paper looks at the strategies adopted by Saudi firms in the manufacturing sector, detailing their corporate-level strategy and business-level strategy. Given an explanation of such strategies, this study aims to evaluate their strategy implementation in terms of success or failure. 62 enterprises from different manufacturing fields in Riyadh are randomly selected as research sample. The data is collected through both structured questionnaires and semi-structured interviews.